The fighting horse of the Stanislaus : stories & essays - De Quille, Dan, 1829-1898 (University of Iowa Press, 1990)
Tongue-Oil Timothy, as unflappable as he is unconscionable, swindles Wasatch Sam in a villainous poker game. Amazed prospectors discover a full-grown silver man deep in a mountain tunnel. Old Pizen, a horse so mean that he was almost poison to himself, is wagered by his own owner in the fight of his life. The travelling stones of Pahranagat, when scattered about the ground, immediately huddle together like eggs in a nest. Highly eccentric but shrewd, itinerant preacher Lorenzo Dow raises the devil. A cheery voiced goblin frog points the way toward the great Comstack silver lode.